Molecular shifts in limb identity underlie development of feathered feet in two domestic avian species - Eric T. Domyan; Zev Kronenberg; Carlos R. Infante; Anna I. Vickrey; Sydney A. Stringham; Rebecca Bruders; Michael W Guernsey; Sungdae Park; J. A. Payne; Robert B. Beckstead; Gabrielle Kardon; Douglas B. Menke; et al. (2016)
Birds display remarkable diversity in the distribution and morphology of scales and feathers on their feet, yet the genetic and developmental mechanisms governing this diversity remain unknown. Domestic pigeons have striking variation in foot feathering within a single species, providing a tractable model to investigate the molecular basis of skin appendage differences. We found that feathered feet in pigeons result from a partial transformation from hindlimb to forelimb identity mediated by cis-regulatory changes in the genes encoding the hindlimb-specific transcription factor Pitx1 and forelimb-specific transcription factor Tbx5. We also found that ectopic expression of Tbx5 is associated with foot feathers in chickens, suggesting similar molecular pathways underlie phenotypic convergence between these two species. These results show how changes in expression of regional patterning genes can generate localized changes in organ fate and morphology, and provide viable molecular mechanisms for diversity in hindlimb scale and feather distribution.